Reactor modeling and kinetic parameters estimation for diethylbenzene (DEB) dehydrogenation reactions - M.E zeynali; H. Abedini; H. R. Sadri (Iranian Journal of Chemical Engineering)
Divinylbenzene (DVB) is produced by catalytic dehydrogenation of DEB at high temperature and atmospheric pressure. Ethylvinylbenzene (EVB) is produced as a useful chemical during dehydrogenation of DEB. Also some other liquid and gaseous by products is produced during dehydrogenation. A set-up has been developed to conduct the DEB dehydrogenation reactions experiments to prepare DVB at different conditions. Model equations for DEB dehydrogenation reactor have been solved by genetic algorithm (GA) method using MATLAB software. Reaction rate constants and absorption coefficients were determined at various temperatures. The conversion of DEB and ethylvinyl benzene (EVB) in the reactor was predicted by mathematical modeling and compared with experimental results. The comparison shows good agreements between experimental and modeling results. The combined effects of DEB flow rate and catalyst weight as time factor were investigated on conversion of DEB and production of EVB and DVB. Effects of temperature on consumption of DEB and production of EVB and DVB in the tubular reactor were investigated.